SYNTHESIS AND CHARACTERIZATION OF SOME NEW TRANSITION METAL COMPLEXES WITH 2,5-di(4-AMINO PHENAZONYL) HEXANE - Al-Hamdani, Abbas Ali Salih (Al-Nahrain Journal of Science, 2010)
A new tetradentate N2O2 type Schiff base ligand 2,5-di(4-amino phenazonyl)hexane L wassynthesized from the condensation of 4-aminophenazone and 2,5-hexanedone. Monomericcomplexes of this ligand, of general formulae [M(L)]X (M-X=Co(II)-(OAc)2, Ni(II)-(OAc)2,Cu(II)-(OAc)2,VO(II)-SO4,Zn(II)-SO4,Mn(II)-Cl2 or Fe(II)-Cl2;OAc=acetate ) are reported. Themode of bonding and overall geometry of the complexes were determined through I.R, UV-Vis,NMR spectral studies, magnetic moment measurements, elemental analysis, metal content andconductance measurement. These studies revealed tetrahedral geometries for the Co(II),Ni(II),Mn(II),Fe(II) and Zn(II) complexes, square pyramidal for VO(II) complex and square planarfor Cu(II) complex. The study of complex formation via molar ratio in DMF solution wasinvestigated and the results were compeer to those found in the solid complexes with a ratio of(M: L) as (1:1)